Effects of a neuromuscular training program on physical performance and asymmetries in female soccer - Roso-Moliner, Alberto; Mainer-Pardos, Elena; Cartón-Llorente, Antonio; Nobari, Hadi; Pettersen, Svein Arne; Lozano, Demetrio (Frontiers in Physiology, 2023)
This research examined the effects of a 10-week neuromuscular training program on physical performance and asymmetries in female football players. Thirty-eight female players from two Spanish Second Division women's football teams participated in the study. The physical performance tests used were: ankle dorsiflexion, bilateral and unilateral horizontal jump, bilateral and unilateral vertical countermovement jump, 40 m sprint including partial times at 10, 20 and 30 m and the 505 test for change of direction evaluation. For ten weeks, players in the experimental group performed three weekly 24-minute neuromuscular training sessions. Participants in the control group completed their normal 24-minute strength and conditioning program. The main results were that maximal linear velocity and change of direction skills showed the most notable improvements (effect size (ES), 0.46 to 0.59) after implementation of the training program, ankle dorsiflexion and jumping skills, also improved although, to a lesser extent (ES, < 0.35) while asymmetries between limbs were reduced. Maximal running speed improved in the intervention group (p<0.001) with a mean ES -0.59. We conclude that a 10-week neuromuscular training program can be a sufficient stimulus to improve football-specific performance variables in high-level female football players. Therefore, female players and coaches should be aware that weekly inclusion of strength, power and dynamic balance exercises following a neuromuscular paradigm is helpful for football-specific performance improvement.